Natural colorant from suji leaves (Pleomale angustivoria) and dragon fruit peel (Hylocereus sp.) - Yeni Rahmawati; Intan Febrianti; Detva Firly Priadi; Orchidea Rachmaniah (Journal of Fundamentals and Applications of Chemical Engineering, 2023)
The application of natural colorant decreases with the increase in synthetic colorant due to its easier to obtain, cheaper, more stable, consistent color, and availability in various color options. However, excessive use of synthetic colorants in the long term may cause either carcinogenic or mutagenic. Therefore, natural colorant research from natural colorants is still promising. Suji leaves (Pleomale angustivoria), and dragon fruit (Hylocereus sp.) peel are potential natural dye sources. The green color of suji leaves is chlorophyll which has been widely used as a natural colorant in food products. In contrast, dragon fruit peel contains betacyanin as an agricultural waste and has not been widely used. Respectively, chlorophyll and betacyanin give green and red colors. They may act as alternatives to natural colorants, safer and healthier than synthetic ones. The research of natural colorants extraction will be carried out in 2 stages; the first is the extraction step of the active natural colorant compounds, i.e., chlorophyll and betacyanin; subsequently, the evaporation of the solvent. Moreover, in the case of betacyanin extract, either citric acid or ascorbic acid is added to pH ± 4.5 as a stabilizer. Dried powder of chlorophyll and betacyanin is also conducted with a simple method as a comparison